Evaluation of genetic alterations of IDH1, TP53 and CASP9 genes as biomarkers in glioma patients - Yit, Pua Jing (2022)
Isocitrate dehydrogenase isoform 1 (IDH1) hotspot mutations are commonly found in gliomas, especially in low-grade gliomas and secondary glioblastoma. The IDH1 p.R132H (c.395G>A) gathered a significant association with clinical outcomes in previous literature. The p53 pathway is usually dysregulated in most of the gliomas. Recent clinical reports showed that glioma patients have the germline mutation of the CASP9 gene and has been observed that the loss of CASP9 occurs in conjunction with several tumor-suppressor genes. The development of gliomas are primarily influenced by a number of significant genetic alterations. However, only a small number of genes were examined in depth. The TP53 and IDH1 genes were noted as having mutations most frequently observed in gliomas. CASP9 gene mutation described in recent clinical reports has illustrated their potential contribution to the gliomagenesis. One of these genes may be a predictive biomarker that may be applied in laboratory settings. To improve early mutation detection for IDH1 hotspot mutation, this study developed tetra primer amplification refractory mutation system polymerase chain reaction (TARMS PCR) assay as a sensitive and specific laboratory testing method to accelerate the process of early screening for glioma. This study identified a novel biomarker in glioma patients through the screening of genetic alteration analysis in all the coding exons in IDH1, TP53 and CASP9 genes. A total of thirty-six (n=36) specimens of hair follicles, blood, and glioma tissue were recruited and analysed using Sanger sequencing. Genetic alterations analysis of the genes of interest were confirmed using Chi-square test and Fisher’s exact test, and bioinformatics analysis from open source databases such as The Cancer Genome Altas (TCGA) and the Chinese Glioma Genome Atlas (CGGA). For the development of the T-ARMS PCR assay, a total of sixty-one (n=61) glioma specimens were collected from the patients to determine their clinical applicability. This study suggested CASP9 p.Q221R (Ex 5 +32G>A) as a novel prognostic biomarker for glioma patients other than the current biomarker of IDH1 p.R132H. A follow-up study was conducted through a semi-quantitative determination of CASP9 protein expression from the glioma tissue and showed a significant difference in the CASP9 protein expression (p=0.024) in the patient group with mutant CASP9 p.Q221R as compared to the wildtype. This study also reported T-ARMS PCR assay is an early screening method with a sensitivity, specificity, and accuracy of 100% (95% CI: 87.94-100.00%), 93.94% (95% CI: 80.39-98.92%) and 96.72%, respectively, and the F1 score of 0.966. A forest plot analysis was used to compare the performance of the T-ARMS PCR assay developed in this study with other published assays. In short, this study demonstrated CASP9 p.Q221R as a novel biomarker for glioma patients besides the current biomarker IDH1 p.R132H and hypothesized to be associated with the survival of glioma patients. The performance of the T-ARMS PCR assay was comparable to the gold standard and could be adapted for preoperative or intraoperative diagnosis as a sensitive and specific screening tool.